An unusual presentation of all the mandibular anterior teeth with two root canals - A case report - Tiku A; Kalaskar R; Damle S (Wolters Kluwer Medknow Publications, 2005)
A rare case of two root canals in all mandibular anterior teeth is presented. The patient initially reported for the treatment of mandibular right central and lateral incisors. However, radiographic evaluation revealed variant root canal and apical foramen patterns.